Preparation and Sound Insulation Performance of Polystyrene Building Flame Retardant and Thermal Insulation Building Materials - Qiulan Guo (International Journal of Analytical Chemistry)
In this study, magnesium hydroxide (MH) was modified by sodium dodecylbenzene sulfonate (SDBS) to prepare modified magnesium hydroxide (MMH) flame retardant, which was mixed with polystyrene (PS) to obtain flame retardant PS composite plate. The micromorphology, mechanical properties, thermal stability, and flame retardancy of flame retardant PS composite plate were analyzed. The experimental results show that MMH is well dispersed in PS matrix, PS-MMH-3 has the best tensile strength and elongation at break, the limit oxygen index (LOI) is 44.3% higher than that of pure PS, and the combustion rate is slow, indicating that PS-MMH-3 has good flame retardant properties.